Singapore perspectives 2012 : Singapore inclusive : bridging divides - Kang, Soon Hock; Leong, Chan-Hoong (World Scientific, 2012)
The Singapore Perspectives series is a yearly publication that provides critical analysis of emerging trends and issues Singapore faces in terms of social, economic and political development. It is a quick and essential reference for understanding the broad policy discussions that animate thought leaders, policy-makers and the public in the country during the immediate period or that are likely to do so in the short and medium term. This edited volume brings together papers presented at the Singapore Perspectives 2012 Conference. The Conference came in the wake of Singapore's General Elections held on May 7, 2011, whose outcome resulted in Singapore's political leaders taking a fresh look at Singapore's public policy. More importantly, the government has pledged to reconnect with all segments of society, as it grapples with the issues that have arisen. Some of the major issues discussed in the book include the widening income gap, the affordability of housing and healthcare, as well as the re-examination of the processes of citizen participation in policy-making. The book also includes the speech made by Mr Tharman Shanmugaratnam, Deputy Prime Minister of Singapore, that outlines his views on the model of governance and policies that would help the country bridge the divides. Co-published by the think-tank, the Institute of Policy Studies, Singapore, this is a useful publication for those with an interest in understanding the governance challenges facing a small, highly globalised economy and nation-state, or those who want a quick feel of the pulse of Singapore.